Globalization and International Relations - Poongulaly, S. (Department of Communication : Parliament of Sri Lanka, 2022)
The concept of globalization is much discussed in political, economic, social, and cultural settings. In fact, globalization seems to have led to the dissolution of global boundaries and the forming of political, economic, social, and cultural linkages between countries. These linkages seem also to be causing political, economic, social and cultural changes, and these changes seem greatly aided by the evolution and spread of communication technologies and mediums, such as mass media, social media, and new media. Particularly, the emergence of social media has not only provided a means for information exchange between global communities but seems also to have caused cultural related changes to the lifestyles of people. In fact, these cultural related changes seem to have gained potential to alter even the historical backgrounds of concerned individuals, specific races or the society at large. As such, it is of interest to understand the changes to cultural practices and lifestyle events as preferred or generated by the people of the Jaffna community due to the use of social media, and on whether such changes are embraced by the whole community. Therefore, to understand this potential impact, popular social media platforms such as Facebook, WhatsApp, Viber and Twitter are investigated under the uses and gratifications theory. On this basis, the consumption of those social media platforms was observed to be on an increasing trend among the Jaffna community, where the continued use and following seems greatly inclined towards being for a mode of gratification. It was also observed that social media platforms tend to partner with specific organizations to instill such social and/or cultural changes for their own economic benefit as well. The author further observed that individuals uploading content regarding their day-to-day activities seem linked to aid business related entities. Moreover, following the consumption of an interested individual’s or organization’s content upload in social media, it was understood from public discussions and social media posts/commentary that people seem to compare such content to their day to day activities and lifestyle, and tend to yearn for those portrayals to be present in their own lives.
Keywords: Globalization; Social Media; International Relations; Technological Advancements; Media Consumption; Jaffna Community; Uses and Gratifications theory